Analysis of EGFR Overexpression, EGFR gene amplification and the EGFRvIII Mutation in portuguese high-grade gliomas - Viana, Marta Pereira (2008)
Background: Patients with malignant gliomas do not respond to any current therapy. Epidermal growth factor receptor (EGFR) controls several oncogenic processes, being frequently up-regulated in gliomas due to overexpression, gene amplification and gene mutation. EGFR inhibitors are being tried in gliomas, yet the molecular determinants of therapeutic response are unclear. Materials and Methods: EGFR overexpression, EGFRvIII mutation and EGFR amplification were determined by immunohistochemistry and chromogenic in situ hybridization (CISH) in 27 primary glioblastomas (GBM), 24 anaplastic oligodendrogliomas (AO) and four anaplastic oligoastrocytomas (AOA). Results: EGFR overexpression was associated with EGFR amplification, being found in 48% and 53% GBM, 33% and 40% AO and 75% and 67% AOA, respectively. EGFRvIII was found in 22% GBM, 8% AO and was absent in AOA. No association was observed between EGFR alterations and patient survival. Conclusion: We characterized, for the first time, EGFR molecular alterations in Portuguese patients with malignant glioma and identified a subpopulation of patients presenting putative biomarkers for EGFR-based therapies.